The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1515/znc-2002-11-1214
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Decomposition of Sporopollenin from Pollen of Typha angustifolia L. by Acidic Methanolysis

Abstract: Sporopollenin from the pollen of Typha angustifolia L. was exposed to a series of 36 subsequent acidic methanolysis procedures. The remaining decomposition products were investigated using several spectroscopic methods including Fourier transform infrared spectroscopy (FT-IR), solid state 13C nuclear magnetic resonance spectroscopy (13C-CPMAS-NMR) and X-ray photoelectron spectrometry (XPS). Substantial weight losses of the sporopollenin material occur after each acidic methanolysis step, while FT-IR and 13C-CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 2 publications
0
67
0
Order By: Relevance
“…Chemical analysis (Rozema et al, 2001;Bubert et al, 2002;Ahlers et al, 2003) and genetic and biochemical studies (Morant et al, 2007;de Azevedo Souza et al, 2009) have demonstrated the presence of lipidic and phenolic units in the sporopollenin polymer. The isolation of numerous mutants affected in exine synthesis has shown, on the other hand, that a large number of genes expressed in the anther tissues participate in the formation of the pollen cell wall, thus suggesting a high degree of complexity of the underlying processes.…”
Section: Discussion Previously Unknown Gene Functions Required For Pomentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical analysis (Rozema et al, 2001;Bubert et al, 2002;Ahlers et al, 2003) and genetic and biochemical studies (Morant et al, 2007;de Azevedo Souza et al, 2009) have demonstrated the presence of lipidic and phenolic units in the sporopollenin polymer. The isolation of numerous mutants affected in exine synthesis has shown, on the other hand, that a large number of genes expressed in the anther tissues participate in the formation of the pollen cell wall, thus suggesting a high degree of complexity of the underlying processes.…”
Section: Discussion Previously Unknown Gene Functions Required For Pomentioning
confidence: 99%
“…At this stage, cellulosic primexine and pectocellulosic intine are produced by the developing microspores and constitute the inner layers of the pollen wall. The outer layer of pollen wall, called the exine, is composed primarily of sporopollenin, a polymer of phenylpropanoid and lipidic monomers covalently coupled by ether and ester linkages (Rozema et al, 2001;Bubert et al, 2002;Ahlers et al, 2003). Sporopollenin precursors are produced in the sporophyte tapetal cell layer surrounding the anther locule, then secreted and deposited on the pollen surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…lap3-2 leads to a wide variety of metabolic consequences in developing anthers. Given the model of sporopollenin composed of fatty acid and phenolic compounds (Guilford et al 1988;Kawase and Takahashi 1995;Ahlers et al 1999Ahlers et al , 2000Ahlers et al , 2003Dominguez et al 1999;MeuterGerhards et al 1999;Bubert et al 2002), it is of interest to note that some changes were detected in the levels of lipids (such as a-linolenic acid, 1-18:3-lysophophatidylethanolamine, 1-16:0-lysophophatidylethanolamine, a-eleosteric acid, and 10E,12Z-octadecadienoic acid, linoleic acid, nonacosane and palmitic acid) and of at least one phenylpropanoid (naringenin chalcone).…”
Section: Lap3 Is Likely Not a Strictosidine Synthasementioning
confidence: 99%
“…In addition, a possibility exists that sporopollenin is not a single substance, but instead varies chemically between species and even between different stages of development (Hemsley et al 1993;Meutergerhards et al 1995). Despite these difficulties, tracer experiments, NMR and spectroscopic/spectrometric studies have yielded a model of sporopollenin composed of polyhydroxylated unbranched aliphatics and phenolics covalently coupled with ether and ester linkages (Guilford et al 1988;Kawase and Takahashi 1995;Ahlers et al 1999Ahlers et al , 2000Ahlers et al , 2003Dominguez et al 1999;Meuter-Gerhards et al 1999;Bubert et al 2002).…”
mentioning
confidence: 99%